1992
DOI: 10.1016/s0309-1651(05)80028-1
|View full text |Cite
|
Sign up to set email alerts
|

DNA polymerase α-primase complex of Physarum polycephalum

Abstract: DNA polymerase alpha and DNA polymerase alpha--primase complex of Physarum polycephalum were purified by rapid methods, and antibodies were raised against the complex. In crude extracts, immune-reactive polypeptides of 220 kDa, 180 kDa, 150 kDa, 140 kDa, 110 kDa, 86 kDa, 57 kDa and 52 kDa were identified. The structural relationships between the 220 kDa, 110 kDa and 140 kDa (the most abundant form) was investigated by peptide mapping. The 140 kDa form was active DNA polymerase alpha. The 57 kDa and the 52 kDa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…The polyanion consists of units of l ‐malate, which are esterified between the hydroxyl group and the β‐carboxyl group to form a linear polyester of a number‐averaged molecular mass of 50 000. It binds replicative DNA polymerases, histones and other nuclear proteins reversibly [5,7–10]. Polymalate synthetase has been studied in vivo [11], but neither the locus nor the proteins involved in the synthesis could be identified.…”
mentioning
confidence: 99%
“…The polyanion consists of units of l ‐malate, which are esterified between the hydroxyl group and the β‐carboxyl group to form a linear polyester of a number‐averaged molecular mass of 50 000. It binds replicative DNA polymerases, histones and other nuclear proteins reversibly [5,7–10]. Polymalate synthetase has been studied in vivo [11], but neither the locus nor the proteins involved in the synthesis could be identified.…”
mentioning
confidence: 99%
“…The nuclear extract contained > 85% of the total nuclear PMLA and > 75% of the total nuclear DNA polymerase activity in the standard assay. Results by SDS/PAGE and Western blotting with specific antisera against DNA polymerases α and ε[13], and DNA polymerase δ[14] were consistent with the recovery of > 95% of DNA polymerase α and > 75% of the other DNA polymerases in the extract.…”
Section: Methodsmentioning
confidence: 78%
“…Nuclear extracts were prepared by incubating for 10 min on ice in an equal volume of extraction buffer (final concentrations 50 mM Tris/HCl pH 7.5, 0.3 M KCl, 20 mM MgCl 2 , 0.5% Triton X-100, 20% glycerol, 1 mM 2-mercaptoethanol, protease inhibitor cocktail) and centrifugation at 700 g. The nuclear extract contained > 85% of the total nuclear PMLA and > 75% of the total nuclear DNA polymerase activity in the standard assay. Results by SDS/ PAGE and Western blotting with specific antisera against DNA polymerases a and e [13], and DNA polymerase d [14] were consistent with the recovery of > 95% of DNA polymerase a and > 75% of the other DNA polymerases in the extract.…”
Section: Preparation Of Nuclear Extractmentioning
confidence: 73%
See 1 more Smart Citation
“…To gain insight into evolutionary variability and synchrony maintenance, we began to characterize the replication apparatus of P. poly- cephalum. DNA polymerase α-primase complex α(140 kDa polymerizing subunit, two primase subunits of 53 and 58 kDa, and a 82 kDa polypeptide) (Weber et al, 1988; Achhammer etal., 1992; ), DNA polymerase δ(125 kDa) and PCNA (35 kDa) (Achhammer et al, 1995) have been identified and characterized. The DNA polymerase α 140 kDa subunit was proteolytically unstable, forming an inactive 110 kDa fragment (Weber et al, 1988).…”
Section: Introductionmentioning
confidence: 99%